Changes in climatic elements and their impact on production of cardamom (Elettaria cardamomum Maton) in the Cardamom Hills of Kerala, India - Joseph, M Murugan, N Mini Raj, Carmel Rani (Journal of Spices and Aromatic Crops, 2000)
The change in climatic elements namely, temperature and precipitation in Cardamom Hills (Kerala, India) was studied by analysing the weather data for 20 (temperature) and 40 years (precipitation). Minimum temperature exhibited drastic variation over the years. The difference betWeen the warmest and coolest month had narrowed considerably and the days have become warmer markedly. Except during 1967-76 (Decade-II) the total annual average precipitation received was more or less equal. Even though the total number of rainy days has increased, the distribution pattern was erratic during the last decade. The rainfall parameters had positive correlation with production of cardamom (Elettaria cardamomum) with significant relationship for number of rainy days.